University students` attitude to e-learning in the post-COVID-19 era - Tomasz Szopiński (Contemporary Economics, 2023)
The study addresses the issue of students' attitudes toward remote learning in a post-COVID-19 reality. It presents the results of a survey conducted in 2023 among students of a Polish university offering online and blended approaches. The analysis of the survey reveals that variables, such as the field of study, the mode of study, the age of the students, and their professional activity, differentiate the frequency of participation in online classes and attitudes towards remote learning. The most conscientious participants in remote classes are part-time students, those working full-time, and those enrolled in legal, political and philological studies. Remote classes were rated highest by students of computer science. In contrast, psychology students and students from the youngest age group were the least active students. Psychology students also rated remote learning the lowest. Respondents' nationality did not differentiate students' attitudes toward remote learning or the frequency of participation.
Keywords: D12; I23; 330; online learning; blended learning; e-learning in higher education; post-COVID reality